SAT-736 Dissecting the Relative Role of Estrogen and Androgen in Fibrosis, Skeletal Muscle Atrophy, and Inguinal Hernia Formation - Zhao, Hong (J Endocr Soc, 2020)
Introduction: More than one in four men develop symptomatic inguinal hernia, and hernia repair is the most commonly performed general surgical procedure in the US. Despite its prevalence, the molecular mechanisms causing inguinal hernia remain unclear. Aromatase, the key enzyme for the conversion of testosterone (T) to estradiol (E2), is present in human but not mouse skeletal muscle tissue. We recently demonstrated that robustly increased local E2 levels in lower abdominal muscle (LAM) tissue and decreased circulating T levels were associated with fibrosis and myocyte atrophy in LAM tissue, leading to severe scrotal (inguinal) hernia formation in a humanized aromatase transgenic mouse model (Arom(hum)) with a high LAM human aromatase expression. To further determine the relative role of estrogen and androgen in the development of inguinal hernia, we generated a novel mild Arom(hum) mouse model with lower LAM aromatase expression compared with the severe model. Methods: Mild Arom(hum) mice were followed for 6 months to determine hernia incidence and measure hernia size (n=30). We treated mild Arom(hum) mice with the aromatase inhibitor, letrozole (n=12) for 12 weeks. Circulating and LAM E2 levels in mice were measured using mass spectrometry. LAM tissue fibrosis and myocyte size were determined by Masson’s trichrome staining and H&E staining, respectively. Results: The mild Arom(hum) mice contain a single copy of the human aromatase genomic fragment with a truncated regulatory region, giving rise to significant but mildly elevated LAM E2 levels (2.5-fold) at 15 weeks of age. Interestingly, these mice maintain normal circulating T levels. Furthermore, we show that mildly increased LAM E2 without decreased circulating T levels cause hernia formation in about 88% of mild Arom(hum) mice in contrast to 100% hernia formation in mice containing the full-length human aromatase regulatory region (severe Arom(hum) model), suggesting that higher LAM estrogen and low serum T levels contribute to this severe phenotype. Treatment with an aromatase inhibitor restores LAM E2 levels to normal levels and completely prevents inguinal hernia formation in the mild Arom(hum) mice. In LAM fibroblasts of mild Arom(hum) mice, we find very high levels of estrogen receptor-α expression, which possibly mediates estrogen-induced hernia formation. Conclusion: Taken together, our findings from the mild Arom(hum) mouse model suggest that lower levels of estrogen excess in LAM are the primary driver of muscle atrophy and hernia formation because this mouse model do not exhibit circulating T deficiency. Our findings will constitute a starting point for dissecting the relative roles of estrogen and androgen action in inguinal hernia development. This has the potential to facilitate drug development to prevent and treat hernias, especially recurrent hernias after primary hernia repairs in vulnerable populations such as elderly men.